Tibetan mineral-herbal medicine Zuotai alleviates the depressive-like behaviors in chronic restraint-stressed mice while regulating stress hormone, inflammation and monoamine - Li, Cen; Niu, Cuiying; Bi, Hongtao; Zhao, Jing; Ivan Alvarez, Jorge; Yuan, Farong; Gai, Xiangyun; Wei, Lixin; Du, Yuzhi; Qiao, Yajun; Kebir, Hania; Xiao, Yuancan; et al. (Frontiers in Pharmacology, 2023)
Zuotai is an ancient mineral-herbal mixture containing β-HgS in Tibetan medicine. It is used to treat nervous system diseases, similar to Chinese medicine cinnabar and Indian Ayurveda medicine Rasasindura. However, one of the key problems faced by Zuotai is that its indications are ambiguous. Our previous study found that Zuotai exhibited the activity of ameliorating depressive-like behaviors in a chronic mild stress model. However, due to the inherent limitations of animal models in simulating human disease, clear results often require more than one model for confirmation. We therefore used another depression model, chronic restraint-stressed (CRS) mice, to validate the antidepression effect of Zuotai. Prophylactic treatment was conducted for 21 consecutive days while mice were subjected to chronic restraint stress. We found that Zuotai and β-HgS ameliorated the anhedonia, behavioral despair, stereotype behavior, and reduction of exploratory and spontaneous movement state of CRS mice. Zuotai and β-HgS also reversed the increases of stress hormone corticosterone (Cort) in serum and pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) in serum and brain, and increased the serotonin（5-HT）in cortex in CRS mice, with positive dose-effect relationship. The Ki67 positive cell number in dentate gyrus and the brain-derived neurotrophic factor (BDNF) in hippocampus slightly were elevated by Zuotai in CRS mice, however that was no statistic difference. Although Zuotai increased total Hg in main organs, it was less than the concentration needed to result in observed adverse effect, at least for kidney and liver; and Zuotai showed no observed adverse effect on the brain histopathology, the cell proliferation in dentate gyrus, as well as the hippocampal and cortical organ coefficients. Conclusively, Zuotai exhibited the alleviation of depressive-like behaviors in CRS mice, accompanying with ameliorating stress hormone, peripherical and cerebral inflammation, and monoamine neurotransmitter.